Derivatives demystified : a step-by-step guide to forwards, futures, swaps and options - Chisholm, Andrew, 1959- (Wiley, 2010)
Derivatives are everywhere in the modern world and it is important for everyone in banking, investment and finance to have a good understanding of the subject. Derivatives Demystified provides a step-by-step guide to the subject, enabling the reader to have a solid, working understanding of key derivative products. Adopting a highly accessible approach, the author explains derivative products in straightforward terms and without the complex mathematics that underlie the subject, focusing on practical applications, case studies and examples of how the products are used to solve real-world probl.